2015
DOI: 10.1038/eye.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of the Retinomax autorefractor for childhood screening validated against a Danish preterm cohort examined at the age of 4 years

Abstract: Background and purpose Refractometers have gained a foothold in childhood screening for ophthalmic disorders. Given the results of an ophthalmic follow-up of an extremely preterm Danish cohort, the results of the Retinomax autorefractor were further evaluated. Materials and methods A nationwide cohort of infants born before gestational age 28 weeks (n = 178) and 56 term controls were examined at the age of 4 years. Refraction was given as the cycloplegic Retinomax value. For this study, we analysed the equipme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
5
10
0
Order By: Relevance
“…The results are in line with a Danish study that found mean visual acuity in extremely preterm children (Fledelius et al. ) to be 0.63 and in full‐term controls 0.8, at 4 years. The frequency of vision impairment in extremely preterm children has been reported as 2.0–3.1% (Leversen et al.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results are in line with a Danish study that found mean visual acuity in extremely preterm children (Fledelius et al. ) to be 0.63 and in full‐term controls 0.8, at 4 years. The frequency of vision impairment in extremely preterm children has been reported as 2.0–3.1% (Leversen et al.…”
Section: Discussionsupporting
confidence: 91%
“…A high number had astigmatism compared to the studies by Fledelius (Fledelius et al. ) (14.6%, cylinder ≥ −0.75D) and Sandfeld (Sandfeld et al. ) (4.3%, cylinder ≥ −1.0D).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations